Characterisation of graphene-based layers for dye-sensitised solar cells application. (1st November 2016) - Lukaszkowicz, K.; Pawlyta, M.; Pasternak, I.; Dobrzański, L.A.; Prokopiuk vel Prokopowicz, M.; Szindler, M.; Drygała, A.; Sitek, J.
Abstract : The influence of the graphene-based counter electrode on the structure, optical properties and electrocatalytic activity of dye-sensitised solar cells (DSCC) was analysed. The graphene and reduced graphene oxide were deposited by CVD and spin-coating method on the FTO glass substrate, respectively. HRTEM investigation confirms the crystallographic structure of graphene. The investigated layers show flat transmittance spectra across the visible and near-infrared region. The charge transfer resistance of the graphene-based film was analysed by electrochemical impedance measurement. The obtained results show the possibility of replacing expensive platinum in DSCC by using graphene-based counter electrode.